Sphingolipid synthesis and role in uterine epithelia proliferation. Issue 2 (August 2018) - Cerbón, Jorge; Baranda-Avila, Noemi; Falcón-Muñoz, Alejandro; Camacho-Arroyo, Ignacio; Cerbón, Marco
Abstract : Sphingolipids are involved in the regulation of cell proliferation. It has been reported that diacylglycerol and sphingosine-1-phosphate generation, during the synthesis of phospho-sphingolipids, is necessary for both, G1-S transition of cell cycle during the sustained activation of protein kinase C in various cell models (MDCK, Saccharomyces and Entamoeba ) and AKT pathway activation. During the estrous cycle of the rat, AKT signaling is the main pathway involved in the regulation of uterine cell proliferation. The aim of the present study was to investigate the role of sphingolipid synthesis during proliferation of uterine cells in the estrous cycle of the rat. On metestrus day, when both luminal and glandular uterine epithelia present the maximal BrdU-labeled cells (S phase cells), there was an increase in the relative abundance of total sphingomyelins, as compared to estrus day. Myriocin, a sphingolipid synthesis inhibitor administered on estrus day, before the new cell cycle of epithelial cells is initiated, decreased the abundance of sphingomyelin, accompanied by proliferation arrest in uterine epithelial cells on metestrus day. In order to study the sphingolipid signaling pathway affected by myriocin, we evaluated the activation of the PKC-AKT-GSK3b-Cyclin D3 pathway. We observed that total and phosphorylated protein kinase C diminished in uterine epithelial cells of myriocin treated animals. Interestingly, cyclin D3 nuclear localization was blocked by myriocin, concomitantly with a decrease in nuclear pRb expression. In conclusion, we demonstrate that sphingolipid synthesis and signaling are involved in uterine epithelial cell proliferation during the estrous cycle of the rat.